A relação entre planejamento e gestão fiscal nos governos estaduais brasileiros - Johanson, Juliani Nunes Campos (2019)
This study aims to analyze whether short term management is driving long term planning in the Brazilian states. From the late 1980s, the literature points to the leading role of fiscal and non-strategic actions in the conduct of public policies, rather than planning towards development. The theoretical approach was made through conceptual discussions about planning and planning, the general characteristics of government planning in Brazil, and the attention given to the transformations that occurred in this process and that changed the logic between planning and planning (management) in the country. In this sense, we assume that short-term management has determined long-term results. The panel is composed of the 26 states of the Brazilian federation plus the Federal District, with data collected from 2001 to 2018. Through the regression methodology with panel data with random effects, the results suggest that long term planning remains deprived of short-term actions, contributing to the study of state managers' reflection on the conduct of public policies.